A review of current evidence about lncRNA MEG3: A tumor suppressor in multiple cancers - Xu, Jie; Wang, Xia; Zhu, Chunming; Wang, Kefeng (Frontiers in Cell and Developmental Biology, 2022)
Long non-coding RNA (lncRNA) maternally expressed gene 3 (MEG3) is a lncRNA located at the DLK1-MEG3 site of human chromosome 14q32.3. The expression of MEG3 in various tumors is substantially lower than that in normal adjacent tissues, and deletion of MEG3 expression is involved in the occurrence of many tumors. The high expression of MEG3 could inhibit the occurrence and development of tumors through several mechanisms, which has become a research hotspot in recent years. As a member of tumor suppressor lncRNAs, MEG3 is expected to be a new target for tumor diagnosis and treatment. This review discusses the molecular mechanisms of MEG3 in different tumors and future challenges for the diagnosis and treatment of cancers through MEG3.